АУЫЗЕКІ ҚЫТАЙ ТІЛІНДЕГІ ҚОЛДАНЫЛАТЫН КОНСТРУКЦИЯЛАР - Қатбаева, Г. Қ. (Journal of Oriental Studies, 2016)
В статье рассматривается часто употребляемые конструкций устной речи китайского языка. In this article it is considered often used construction of oral speech of the Chinese language.